Steel material joined body and manufacturing method thereof
The steel joint manufacturing method involves using a carbonaceous material and heating stainless steel materials to create a concentration gradient layer, effectively enhancing bonding ratios and strengths between stainless steel materials.
Patent Information
- Application Number
- JP2023172408
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Existing methods for manufacturing steel joints between stainless steel materials struggle to achieve high bonding ratios and bonding strengths.
A steel joint manufacturing method where stainless steel materials are joined with a carbonaceous material at the bonding interface, heated to a maximum temperature of 1200° C. to 1500° C., and processed to create a concentration gradient layer with maximum carbon concentration at the interface, decreasing as it moves away.
This method achieves high bonding ratios and bonding strengths between stainless steel materials, improving ductility and toughness at the bonding interface.
Smart Images

Figure 2025063346000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel member joint and a method for manufacturing the same. [Background technology]
[0002] There is known a method for manufacturing a joined steel member in which the joining surfaces of steel members to be joined via a carbonaceous material are overlapped and heated (see Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-7970 [Patent Document 2] Japanese Patent Application Publication No. 57-22867 [Patent Document 3] JP 2023-39175 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the inventions described in Patent Documents 1 to 3 have limitations in achieving a high joining rate and joining strength between stainless steel materials. Therefore, an object of the present invention is to provide a joined steel member that achieves a high joining rate and joining strength between stainless steel members, and a method for manufacturing the same. [Means for solving the problem]
[0005] The steel joint of the present invention is a steel joint in which a plurality of stainless steel materials are joined together, and has a concentration gradient layer in which the carbon concentration at the joint interface between the stainless steel materials is at a maximum value and decreases with increasing distance from the joint interface.
[0006] The manufacturing method of a steel material joint according to the present invention is a manufacturing method of a steel material joint in which a plurality of stainless steel materials are joined together, and includes a placement step of placing a carbonaceous material on at least one of the joining surfaces of the stainless steel materials to be joined, a superposition step of overlapping the joining surfaces of the stainless steel materials to be joined with the carbonaceous material interposed therebetween, and a heating step of heating the stainless steel materials with the overlapped joining surfaces at a maximum temperature of 1200°C or more and 1500°C or less. The maximum temperature is preferably 1300°C or higher and 1500°C or lower. Effect of the Invention
[0007] According to the present invention, there is provided a joined steel member in which a high joining rate and joining strength between stainless steel members is achieved, and a method for manufacturing the same. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a conceptual diagram for explaining a steel joint according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a process flow diagram for explaining a method for manufacturing a steel joint according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a conceptual diagram for illustrating a method for manufacturing a steel joint according to a first specific embodiment of the present invention. [Figure 4] FIG. 6 is a conceptual diagram for illustrating a method for manufacturing a steel joint according to a second specific embodiment of the present invention. [Diagram 5] 1 is an iron-carbon phase diagram (corresponding to SUS304) for explaining the effect of the present invention when the heating temperature is 1300° C. or higher. [Figure 6] FIG. 2 is a conceptual diagram for explaining the effect of the present invention when the heating temperature is 1300° C. or higher. [Figure 7] 11A and 11B are diagrams for explaining an observation position when checking a joining rate and a method of calculating the joining rate. [Figure 8] FIG. 2 is a conceptual diagram showing the results of distribution of carbon amount and hardness from a joint interface in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. FIG. 1 is a conceptual diagram for explaining a steel member joint according to the present embodiment. In the steel joint 1 according to the present embodiment, as shown in Fig. 1, a plurality of stainless steel materials 10, 20 are joined together. The carbon concentration (carbon concentration A shown in Fig. 1) at a joint interface 30 where the plurality of stainless steel materials 10, 20 (hereinafter also referred to as "materials") are joined together is a maximum value. Furthermore, the joint interface 30 has concentration gradient layers 15, 25 in which the carbon concentration decreases with increasing distance from the joint interface 30.
[0010] In the joined steel body 1 according to this embodiment, the carbon concentration at the joint interface 30 is at a maximum value, and therefore the stainless steel materials 10, 20 have a high joining rate and joint strength. Furthermore, since the steel joint 1 according to this embodiment has concentration gradient layers 15, 25, the carbon concentration (carbon concentration B in FIG. 1) on the side opposite to the joint interface 30 in the concentration gradient layers 15, 25 (the side of the steel materials (materials 10, 20) before joining) is lower than that at the joint interface 30. Therefore, the materials 10, 20 side can exhibit "elongation." From the above, the steel joint 1 according to this embodiment can be suitably used in applications where "elongation" is required on the materials 10, 20 side.
[0011] As shown in FIG. 1, the concentration gradient layers 15 and 25 preferably have a carbon concentration that decreases continuously with increasing distance from the bonded interface 30 . In the present invention, the term "continuously decreasing" refers to a proportional decrease in the carbon concentration value from the bonded interface 30 toward the multiple stainless steel materials (raw materials) 10, 20 as shown in FIG. Since the concentration gradient layers 15, 25 have such a decreasing tendency, in addition to the above-mentioned effects, the ductility and toughness at the joint interface 30 are also improved.
[0012] The carbon concentration at the joint interface 30 in the joined steel member 1 according to this embodiment can be measured by cutting the joined steel member 1 along the joint interface 30, polishing the cross section, and measuring the carbon concentration using an element distribution measuring device such as an electron probe microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX). In the present invention, the carbon concentration at the joint interface 30 is calculated by averaging measurements taken at any five points on the polished cross section.
[0013] The carbon concentration of the concentration gradient layers 15, 25 in the steel joint 1 according to this embodiment can be measured by cutting the steel joint 1 along the joint interface 30, then further cutting it in a direction away from the cut surface of the joint interface 30 (towards the materials 10, 20), and then polishing the cross section cut in the direction away. The carbon concentration can be measured using an element distribution measuring device such as an electron probe microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX).
[0014] In the present invention, the decreasing tendency of the concentration gradient layers 15, 25 can be measured by measuring the carbon concentration at any five points (10 points in total) on a straight line from the carbon concentration at the bonded interface 30 to the carbon concentration at the materials 10, 20 in each direction from the bonded interface 30 to the materials 10, 20 on a polished cross section in the separating direction using an element distribution measuring device as described above, and creating a graph as shown in FIG. 1 in which the carbon concentration is plotted against the distance, with the distance from the bonded interface 30 on the horizontal axis and the carbon concentration on the vertical axis.
[0015] In the joined steel body 1 according to this embodiment and its manufacturing method described later, the stainless steel materials (raw materials) 10, 20 to be joined are, for example, austenitic stainless steels as defined by JIS, such as SUS304, SUS316, SUS304L, and SUS316L. The stainless steel materials (base materials) 10, 20 to be joined are preferably SUS304. In the case of SUS304, a steel joint can be reliably obtained in which a high joining rate and joining strength between stainless steel members is achieved.
[0016] The shape of the multiple stainless steel materials (raw materials) 10, 20 before joining is not particularly limited as long as they each have a joining surface and can be integrated with each other by overlapping these joining surfaces. The stainless steel materials (raw materials) 10, 20 can be, for example, a cylindrical shape, a rectangular column shape, a screw shape, a concave-convex shape, etc.
[0017] FIG. 2 is a process flow diagram for illustrating the method for manufacturing a steel joint according to the embodiment of the present invention. The method for manufacturing a steel member according to this embodiment is a method for manufacturing a steel member in which a plurality of stainless steel materials are joined together, as shown in FIG. 2, and includes an arrangement step S100 of arranging a carbonaceous material on at least one of the joining surfaces of the stainless steel materials to be joined, a superposition step S110 of overlapping the joining surfaces of the stainless steel materials to be joined described above with the carbonaceous material interposed therebetween, and a heating step S120 of heating the stainless steel materials with the overlapped joining surfaces at a maximum temperature of 1200° C. or more and 1500° C. or less. The manufacturing method of the steel member joint according to the present invention includes the above-mentioned process flow, and thus can achieve a high joining rate and joining strength between stainless steel members.
[0018] Each of these steps will now be described in detail. Fig. 3 is a conceptual diagram for explaining a method for manufacturing a joined steel member according to a specific first embodiment of the present invention. Fig. 4 is a conceptual diagram for explaining a method for manufacturing a joined steel member according to a specific second embodiment of the present invention. The first embodiment shown in Fig. 3 and the second embodiment shown in Fig. 4 differ only in the form of the carbonaceous material placed on the joining surfaces of the stainless steel members.
[0019] <Regarding the placement process S100> In the manufacturing method of the joined steel member according to the present embodiment, in the arrangement step S100, as shown in Fig. 3(a) and Fig. 4(a), a carbonaceous material (35 (powdered carbonaceous material) or 40 (sheet-like carbonaceous material: hereinafter also referred to as graphite sheet) is arranged on at least one of the joining surfaces (10a and / or 20a: one of the joining surfaces in Fig. 3(a) and Fig. 4(a)) of the stainless steel materials 10, 20 to be joined.
[0020] The carbonaceous materials 35, 40 can be placed on at least one of the joining surfaces (10a and / or 20a) of the stainless steel members 10, 20 to be joined, and the material and shape are not particularly limited as long as the joining surfaces (10a and 20a) can be integrated. For example, a powdered carbonaceous material 35 shown in FIG. 3 or a sheet-like carbonaceous material 40 shown in FIG. 4 can be used. Here, when a powdered carbonaceous material 35 is used, it can be placed by applying it to the joining surfaces (10a and / or 20a). When a sheet-like carbonaceous material 40 is used, it can be placed directly on the joining surfaces (10a and / or 20a) via, for example, double-sided tape or the like.
[0021] <About the overlapping step S110> In the manufacturing method of the joined steel member according to the present embodiment, in a superposing step S110, the joining surfaces (10a and 20a) of the stainless steel materials 10 and 20 to be joined are superposed on each other via the carbonaceous material (35 or 40) arranged in the arrangement step S100, as shown in Fig. 3(b) and Fig. 4(b). In this superposing step S110, when the joining surfaces (10a and 20a) of the stainless steel materials 10 and 20 are superposed on each other, it is preferable to apply a load to fix the joining surfaces to each other. In the overlapping process S110 of this embodiment, by applying a load to fix the joining surfaces (10a and 20a) of the stainless steel materials 10, 20 to each other, it is possible to increase the joining rate and joining strength between the stainless steel materials (10 and 20).
[0022] <About the heating step S120> In the manufacturing method of a steel joint according to this embodiment, in the heating step S120, the stainless steel materials 10, 20 whose joining surfaces (10a and 20a) have been overlapped in the overlapping step S110 are heated as shown in Figures 3(c) and 4(c).
[0023] In addition, in this heating step S120, it is preferable to apply a load to fix the joining surfaces (10a and 20a) of the stainless steel materials 10, 20 together when the heating is performed. In the heating process S120 of this embodiment, by applying a load to fix the joining surfaces (10a and 20a) of the stainless steel materials 10, 20 together, the joining rate and joining strength between the stainless steel materials (10 and 20) can be increased.
[0024] The heating is performed at a maximum temperature of 1200° C. or more and 1500° C. or less. When the heating temperature is less than 1200° C., the joining rate may decrease due to the low heating temperature, whereas when the heating temperature exceeds 1500° C., the heating may not be optimally performed due to the possibility of thermal deformation of other members that fix the steel joint during heating.
[0025] The heating is preferably performed at a maximum temperature of 1300° C. or higher and 1500° C. or lower. Fig. 5 is an iron-carbon phase diagram (equivalent to SUS304) for explaining the effect of the present invention when the heating temperature is 1300°C or higher. Fig. 6 is a conceptual diagram for explaining the effect of the present invention when the heating temperature is 1300°C or higher. That is, in the manufacturing method of the steel member according to this embodiment, carbon powder (carbonaceous material) is placed on at least one of the joining surfaces of the stainless steel members to be joined, and the steel members, with the joining surfaces of the stainless steel members to be joined overlapped with each other via this carbonaceous material, are heated in a predetermined atmosphere (e.g., in a nitrogen atmosphere) at a maximum temperature of 1300°C or more and 1500°C or less (see FIG. 6(a)).
[0026] When the temperature of the joint surface between the stainless steel materials reaches 1300°C, a liquid phase (hereafter referred to as "L") with a carbon concentration of 2.5 mass% is generated at the interface between the steel material and the carbonaceous material (see the part indicated by the square in Figure 5). This liquid phase L increases until the carbonaceous material disappears (see Figure 6(b)). At 1300°C, the carbon concentration at the interface between the "liquid phase L+FCC (austenite phase)" region and the "austenite phase" region (see the part marked with a circle in Figure 5) is 0.5 mass% (see Figure 5). Carbon diffusion at 1300°C is extremely fast, and when maintained at this temperature, carbon diffuses at a high speed from the joining surface of the steel materials into the internal austenite phase. As a result, at the interface between the liquid phase L and the austenite, the austenite phase side tries to maintain the carbon concentration at 0.5 mass%, stealing carbon from the liquid phase L side. Meanwhile, the liquid phase L tries to maintain the carbon concentration at 2.5 mass%, so the liquid phase L decreases (see Figure 6(c)). Finally, the liquid phase L disappears and the joining of the steel materials is completed (see Figure 6(d)). As described above, by setting the maximum temperature to 1300°C or higher, the generation of carbides and the like (for example, symbol α (M7C3: carbide) in Figure 5) at the joint 50 during the heating process S120 can be suppressed, thereby further increasing the joining rate and joining strength between the stainless steel materials.
[0027] The heating means in the heating step S120 is not particularly limited as long as it does not impair the effects of the present invention, and various heating methods can be used, such as high-frequency induction heating 100 using a conventionally known heating coil 60, a heating furnace other than high-frequency induction heating, laser heating, etc. Furthermore, the atmosphere during heating in the heating step S120 is not particularly limited. The atmosphere includes, for example, an oxidizing atmosphere (oxygen, air, etc.) and a non-oxidizing atmosphere (nitrogen, argon, etc.).
[0028] The heating step S120 of the present invention is preferably performed by high-frequency induction heating 100. Since the high-frequency induction heating 100 can accurately and rapidly heat to a desired temperature, it is easy to manufacture the above-mentioned joined steel body 1.
[0029] Then, in the heating step S120 of the present invention, when the liquid phase L generated at the joining surface 50 of the steel materials 10, 20 disappears, the steel materials (10 and 20) are joined together (FIGS. 3(d) and 4(d)). The cooling means after the heating in the heating step S120 of the present invention is not particularly limited, and conventionally known gas cooling, spray cooling using a coolant such as a polymer, natural cooling, etc. can be used.
[0030] The maximum temperature reached in the heating step S120 of the present invention can be measured by a platinum-rhodium thermocouple welded to the outer circumferential surface of the steel material (raw material) side within 2 mm from the joining surface 50 of the stainless steel materials to be joined.
[0031] The present invention will now be described in more detail with reference to examples and comparative examples, although the present invention is not limited to these examples in any way. EXAMPLES
[0032] Example 1 In Example 1, two pieces of SUS304 having the chemical composition (unit: mass%) shown in Table 1 and the cylindrical shape shown in FIG. 1 (length X: 150 mm, diameter T: 15 mm (50 mm diameter of joining surface)) were prepared. [Table 1] Then, these two pieces of SUS304 were joined together to prepare a steel joint as shown by reference number 1 in Fig. 1 as a test specimen. At this time, a graphite sheet (graphite thickness 10 μm, double-sided tape thickness 6 μm: total thickness 16 μm) was placed on the joining surfaces of the two pieces of SUS304, and the joining surfaces of the steel materials to be joined via this carbonaceous material were overlapped. Next, high-frequency induction heating was performed in a nitrogen gas atmosphere at a frequency of 5.5 kHz, a pressurizing pressure of 7.1 MPa, and a maximum temperature of 1200°C, and then the steel was allowed to cool.
[0033] Comparative Example 1 A steel joint as shown by reference numeral 1 in FIG. 1 was produced under the same conditions as in Example 1, except that a Zn foil (thickness: 50 μm) was used instead of the graphite sheet. Comparative Example 2 A steel joint as shown by reference numeral 1 in FIG. 1 was produced under the same conditions as in Example 1, except that a Sn foil (thickness 10 μm) was used instead of the graphite sheet.
[0034] In the above Example 1 and Comparative Examples 1 and 2, the bonding ratio of the prepared test specimens (steel bonded bodies) was evaluated. Here, the joining rate was confirmed by observing the joining interface of the obtained steel member joint of Example 1 in a non-etched state with an optical microscope. Fig. 7 is a diagram for explaining the observation position when confirming the joining rate and the method of calculating the joining rate.
[0035] As shown in Fig. 7, the observation position for checking the joining rate was the state where the steel joint was cut at an L cross section parallel to the central axis α as shown in Fig. 7, and the joining rate was calculated as "(d-ΣLv) / d×100" using the values where d is the diameter of the steel joint and Lv is the length of the void as shown in Fig. 7. Table 2 below shows the results of checking the joining rate together with other results.
[0036] [Table 2]
[0037] As shown in Table 2, Example 1 was able to achieve a bonding rate of 99.9%. Furthermore, the test specimens (steel joints) produced in Example 1 were checked for the presence or absence of a concentration gradient layer (a concentration gradient layer in which the carbon concentration decreases with increasing distance from the joint interface) and for the joint strength. The presence or absence of a concentration gradient layer was determined by creating a graph as shown in FIG. 1, in which the carbon concentration is plotted against the above-mentioned distance, and then checking whether or not there is a tendency for the carbon concentration to decrease. The joint strength was measured and evaluated as tensile strength. This tensile strength was tested using JIS No. 9A (G.L 100mm).
[0038] FIG. 8 is a conceptual diagram showing the results of carbon amount and hardness distribution from the bonded interface in Example 1. 8, a concentration gradient layer was confirmed in Example 1, in which the carbon concentration was maximum at the bonded interface and decreased with increasing distance from the bonded interface. The same tendency as the carbon concentration profile was also confirmed in the bond strength. From the above results, it was confirmed that in this embodiment, a steel joint having a high joining rate and high joining strength at the joining interface can be obtained. [Industrial Applicability]
[0039] According to the joined steel member and the manufacturing method thereof of the present invention, a high joining rate and joining strength between stainless steel members can be achieved. Therefore, the method for manufacturing a steel member joint according to the present invention can be suitably employed in the manufacture of various structures including a steel member joint. [Explanation of symbols]
[0040] 1 Steel joint 10 Stainless steel material (material) 10a Joint surface 15 Concentration gradient layer 20 Stainless steel 20a Joint surface 25 Concentration gradient layer 30 Joint interface 35 Carbonaceous materials 40 Carbonaceous materials 50 Joint 100 High frequency induction heating S100 placement process S110 Stacking process S120 Heating process A Carbon concentration (joint interface) B Carbon concentration (opposite side of the concentration gradient layer from the bonding interface) T diameter (steel material) L liquid phase
Claims
1. A steel joint in which a plurality of stainless steel materials are joined together, The carbon concentration at the joint interface between the stainless steel materials is a maximum value, A joint of steel members having a concentration gradient layer in which the carbon concentration decreases with increasing distance from the joint interface.
2. A method for manufacturing a steel material joint in which a plurality of stainless steel materials are joined together, comprising the steps of: A disposing step of disposing a carbonaceous material on at least one of the joining surfaces of the stainless steel members to be joined; a lamination step of laminating the joining surfaces of the stainless steel materials to be joined together via the carbonaceous material; and a heating step of heating the stainless steel members with the joining surfaces overlapped to a maximum temperature of 1200°C or higher and 1500°C or lower.
3. The method for producing a steel member joint according to claim 2, wherein the maximum temperature is 1300°C or higher and 1500°C or lower.
Citation Information
Patent Citations
Diffusion brazing method of steel
JP1982022867A
Hot joining method for steel
JP1994007970A
Method for producing steel material conjugant
JP2023039175A